INTERNAL MARKETING MIX PADA KINERJA TENAGA KEPENDIDIKAN UNIVERSITAS SEBELAS MARET - Pratiwi, Desi Sanggar; Haryanto, Budhi (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This study examines the influence of Internal Marketing Mix that includes Top Management Support Mix, Bussines Support Mix and Cross Coordination on employee performance. The sample of this research is about 200 education staff of Sebelas Maret University. This research uses analysis method in the form of Path Analysis with SPSS analysis tool 22. The result of research analysis shows that Top Management Support Mix, Bussines Support Mix influence to the performance of education personnel. While Cross Functional Coordination as a component of Internal Marketing Mix does not affect the performance of educational personnel. This research provides advice to university leaders to improve top management support and support on the service process so that the performance of education personnel. As well as suggestions for future similar research to expand the scope of the research to be not limited only to educational personnel in one university.